Functioning features of industrial enterprises and complexes in modern economic conditions: structural changes and industrial development prospects - O. E. Astafyeva (Вестник университета)
The article presents an analysis that contains functioning features of industrial enterprises and complexes in the conditions of transformation of their activities caused by the fourth industrial revolution. The purpose of the study is to determine the significance of structural changes in industry and the role of industrial policy in the implementation of structural transformations that contribute to the sustainable development of the economy. During the set goal, the objectives of the study were identified, which are necessary to coordinate industrial development programs in related sectors of the economy, modernization of infrastructure that promotes industrial development on a platform basis and the effectiveness of industrial policy implemented at the state level. When studying the task, methods of system and structural analysis, a structural-functional approach to the analysis of structural change problems were used. As a result of the study, it was revealed that the currently implemented programs of enterprise development should be coordinated with the strategies for the development of industries, which will allow them to coordinate and determine the levels and ways of interaction of economic entities. The directions of structural changes are proposed as a response to the digitalization of production processes and a way of rational organization of economic activity of subjects.